Economic Reform in China : A New Phase - Burton, David (Occasional Papers; Occasional Paper ;, 1994)
China's economic performance hs been remarkable since the the reform process began 15 years ago. Notwithstanding the achievements that have been made, a number of serious problems remain. This papers discusses the current reform program and the effors being made to overcome the structural impediments to growth.